Correlation between neutrophil gelatinase phase lipocalin and cerebral small vessel disease - Yang, Ying-hao; Li, Shan-shan; Wang, Yun-chao; Yu, Lu-lu; Zhu, Hang-hang; Wu, Jing-hao; Yu, Wen-kai; An, Lu; Yuan, Wen-xin; Ji, Yan; Xu, Yu-ming; Gao, Yuan; et al. (Frontiers in Neurology, 2023)
Background Cerebral small vessel disease (CSVD) is common in the elderly population. Neutrophil gelatinase-associated lipocalin (NGAL) is closely related to cardiovascular and cerebrovascular diseases. NGAL causes pathological changes, such as damage to the vascular endothelium, by causing inflammation, which results in other related diseases. The purpose of this study was to investigate whether serum NGAL levels could predict disease severity in patients with CSVD. Methods The patients with CSVD who visited the Department of Neurology at the First Affiliated Hospital of Zhengzhou University between January 2018 and June 2022 were prospectively included. The total CSVD burden score was calculated using whole-brain magnetic resonance imaging (MRI), and the patients were divided into a mild group (total CSVD burden score < 2 points) and a severe group (total CSVD burden score ≥ 2 points). Age, sex, height, smoking and alcohol consumption history, medical history, and serological results of patients were collected to perform the univariate analysis. Multivariate logistic regression was used to analyze the risk factors that affect CSVD severity. The multiple linear regression method was used to analyze which individual CSVD markers (periventricular white matter hyperintensities, deep white matter hyperintensities, lacune, and cerebral microbleed) play a role in the association between total CSVD burden score and NGAL. Results A total of 427 patients with CSVD (140 in the mild group and 287 in the severe group) were included in the study. A multivariate logistic regression analysis showed that the following factors were significantly associated with CSVD severity: male sex [odds ratio(OR), 1.912; 95% confidence interval (CI), 1.150–3.179], age (OR, 1.046; 95% CI, 1.022–1.070), history of cerebrovascular disease (OR, 3.050; 95% CI, 1.764–5.274), serum NGAL level (OR, 1.005; 95% CI, 1.002–1.008), and diabetes (OR, 2.593; 95% CI, 1.424–4.722). A multivariate linear regression shows that periventricular white matter hyperintensities and cerebral microbleed are associated with serum NGAL concentrations (P < 0.05). Conclusion Serum NGAL level is closely related to CSVD severity and is a risk factor for the burden of CSVD brain damage. Serum NGAL has high specificity in reflecting the severity of CSVD.